Trends in radiotherapy administration in the management of hepatocellular carcinoma: Analysis of a Korean tertiary hospital registry of hepatocellular carcinoma patients diagnosed between 2005 and 2017 - Bae, Bong Kyung; Park, Hee Chul; Yu, Jeong Il; Yoo, Gyu Sang; Sinn, Dong Hyun; Choi, Moon Seok; Oh, Joo Hyun (Frontiers in Oncology, 2022)
Purpose: To present the trends in radiotherapy for the management of hepatocellular carcinoma (HCC) at a single tertiary referral hospital in South Korea. Materials and Methods: We retrospectively reviewed prospectively collected registry data of patients newly diagnosed with HCC between January 2005 and December 2017 at the Samsung Medical Center. Trends in radiotherapy, delivery techniques, tumor stage, and age were evaluated. Results: During the study period, 9,132 patients were newly diagnosed with HCC at our institution. Of these, 2,445 patients (26.8%) received radiotherapy for all lesions, including extrahepatic metastases; 1,865 patients (20.4%) received radiotherapy for intrahepatic lesions alone, and 469 patients (5.1%) received radiotherapy as initial management. Although the proportion of patients receiving radiotherapy increased slightly over the study period (24.2% vs. 26.6%), the proportions of patients receiving radiotherapy for intrahepatic lesions (16.8% vs. 21.9%) and as initial management (0.1% vs. 12.5%) increased dramatically. The majority of patients treated between 2005 and 2008 received three-dimensional conformal radiotherapy (56.3%), whereas the majority of patients treated between 2018 and 2021 received proton beam therapy (43.6%). With the technical developments, the overall survival (OS) of patients who received radiotherapy as initial management increased significantly (5-year OS: from 5.4% to 30.1%), and the OS difference between patients who did and did not receive radiotherapy as initial management significantly decreased (ratio of restricted mean survival time: from 0.383 to 0.544). Conclusion: This registry-based, retrospective study indicated an increasing trend in the utilization of radiotherapy, adoption of advanced radiotherapy techniques, and OS improvements in patients with HCC.